Plugging agent for repairing building roofs and preparation method thereof
By using a leak plugging agent with a combination of specific ingredients, the problems of long curing time and poor chemical corrosion in the prior art are solved, and the effects of rapid air-drying at room temperature and good chemical corrosion resistance are achieved, reducing the environment and human body The dangers of health.
Patent Information
- Application Number
- CN202411474268.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The leak plugging agent used for existing roof repairs has a long curing time, which affects the progress of the project, and is not good under high temperature, high humidity and chemical corrosion. It contains volatile organic compounds that are harmful to the environment and human health.
Use 30-45% hydroxyethyl cellulose modified polyurethane resin, 15-30% acrylic acid, 2-5% quartz sand, 2-5% talc, 15-20% xanthan gum, 1-3% phenylbenzene Combination of niimidazole, 1-3% benzophenone-1, 2-5% green tea extract, 10-15% vinyl siloxane, 1-3% butyl hydroxytoluene and other components through specific preparation methods A leak plugging agent that can quickly air-dry at room temperature and has good chemical corrosion and waterproofing properties is prepared.
It realizes formaldehyde-free leak plugging agent, reduces potential harm to the environment and human health, has fast curing, good waterproof and chemical corrosion resistance, and extends its service life.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of leak-proofing agents, and in particular relates to a leak-proofing agent for repairing a building roof and a preparation method thereof. Background Art
[0002] With the acceleration of industrialization, the frequency of use of various equipment and pipelines has increased, and problems such as water leakage and oil leakage have become increasingly serious. Effective plugging materials are urgently needed to solve these problems. With the rapid development of the construction industry, the demand for waterproofing and plugging materials has increased significantly. The maintenance and renovation of old facilities have also made plugging agents an important part of maintaining infrastructure; with the development of materials science and chemical technology, the application of new materials such as polymers, epoxy resins and other materials has promoted the research and development of plugging agents to a further level, making the performance of plugging agents more superior. With the enhancement of environmental awareness, the market demand for non-toxic and harmless plugging agents has increased, which has promoted the development of green plugging materials.
[0003] At present, the development of plugging agents has achieved phased results, but the curing time of existing plugging agents for roof repair is relatively long, which will cause delays in the renovation of old houses and affect the progress of the project. In addition, the existing plugging agents for roof repair do not perform well under high temperature, high humidity and chemical corrosion, which will lead to a short service life after repair. At the same time, they contain volatile organic compounds or other harmful components, which will have a harmful effect on the environment and human health. The Chinese patent with publication number CN108585735A discloses a plugging agent and a preparation method thereof. Although it can effectively solve the problem of water and oil leakage in houses, its preparation process is complicated and it contains volatile organic compounds, which are harmful to the environment and human body during use. The Chinese patent with publication number CN106614380A discloses a method for preparing a house plugging agent using modified grapefruit peel. Although there are no volatile organic compounds during use, its chemical corrosion resistance is poor, and it is difficult to effectively maintain the plugging effect in long-term use.
[0004] In view of the above technical defects, a solution is now proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a leak-proofing agent for repairing building roofs and a preparation method thereof, which does not contain harmful volatile organic compounds such as formaldehyde, has no potential harm to human health, can be quickly air-dried at room temperature, and has strong chemical corrosiveness.
[0006] To achieve the above purpose, the present invention adopts the following technical scheme: a leak-proof agent for repairing building roofs is composed of the following percentage components: 30-45% hydroxyethyl cellulose modified polyurethane resin, 15-30% acrylic acid, 2-5% quartz sand, 2-5% talcum powder, 15-20% xanthan gum, 1-3% phenylbenzimidazole, 1-3% benzophenone-1, 2-5% green tea extract, 10-15% vinyl siloxane, 1-3% butylated hydroxytoluene;
[0007] Furthermore, the preparation method of the hydroxyethyl cellulose modified polyurethane resin comprises the following steps:
[0008] A1: Add polyurethane resin and 9% hydrochloric acid into an oil bath pot, install a thermometer and a magnetic stirrer in the oil bath pot, adjust the oil bath temperature to 80-90°C, heat the oil bath, adjust the magnetic stirrer stirring rate to 400-500rpm, stir for acid hydrolysis reaction for 30min, adjust the temperature to 50-65°C, set the stirring rate to 300-400rpm, and stir for 1h to obtain intermediate A;
[0009] A2: Add hydroxyethyl cellulose to intermediate A, use a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, fill with nitrogen protection, stir and react for 0.5 h at a temperature of 30-40°C and a stirring rate of 300-400 rpm, then heat to 80-90°C for reflux reaction for 2-3 h, use a magnetic stirrer with a speed of 200-300 rpm to continuously stir during the reflux reaction, let it stand after the reflux reaction is completed, observe the thermometer reading, stop standing when the thermometer reading drops to 25°C, then use a vacuum filter to vacuum filter, wash the filter cake with distilled water for 3-5 times, then place it in a vacuum drying oven, and dry it at a temperature of 80-85°C for 0.5-1h to obtain intermediate B;
[0010] A3: Transfer intermediate B to a distillation tower, adjust the pressure of the distillation tower to 0.2-0.5 atm, and collect the distillation bottom product after distillation for 3-5 hours; repeat steps A1-A2 twice for the top product of the distillation tower, transfer the distillation bottom product to room temperature and cool it for 0.5-1 hour to obtain a hydroxyethyl cellulose modified polyurethane resin.
[0011] Furthermore, the mass ratio of the polyurethane resin and 9% hydrochloric acid in step A1 is 1:5; the mass ratio of the intermediate A and hydroxyethyl cellulose in step A2 is 3:1;
[0012] Furthermore, a method for preparing a leak-proofing agent for repairing a building roof comprises the following steps:
[0013] B1: Preparation of hydroxyethyl cellulose modified polyurethane resin;
[0014] B2: Add hydroxyethyl cellulose modified polyurethane resin, acrylic acid and xanthan gum into the reactor, adjust the reaction temperature to 80-100°C, set the speed of the magnetic stirrer to 1000-1200 rpm and stir for 30 min, then add vinyl siloxane, continue stirring and reacting for 1 h to obtain product 1;
[0015] B3: Product 1 was transferred to a high-pressure reactor, and then quartz sand and talcum powder were added to the reactor, the pressure of the high-pressure reactor was adjusted to 5.8-6.5 MPa, the temperature was adjusted to 65-80°C, and the speed of the magnetic stirrer was set to 1500-1800 rpm and stirred for 30 min to obtain product 2;
[0016] B4: Add phenylbenzimidazole and benzophenone-1 to product 2, keep the pressure of the autoclave unchanged, adjust the reaction temperature to 45-52°C, set the speed of the magnetic stirrer to 800-1000 rpm, and stir for 30 minutes to obtain product 3;
[0017] B5: Add green tea extract and butylated hydroxytoluene to product 3, adjust the pressure of the autoclave to 3.4-4.2 MPa, the temperature to 54-62°C, and the speed of the magnetic stirrer to 600-800 rpm. After stirring for 30 minutes, let it stand at normal pressure (0.1013 MPa) for 15 minutes to obtain a plugging agent for repairing building roofs.
[0018] Furthermore, the green tea extract is a water-soluble green tea extract powder with a specification of 15:1; the talcum powder is a talcum powder with a silicon content of 60% and a particle size of 2000 mesh; and the quartz sand is a quartz sand powder with a silicon dioxide content of 99% and a particle size of 2000 mesh.
[0019] In summary, due to the adoption of the above technical scheme, the beneficial effects of the present invention are as follows: the leak-proof agent of the present invention does not contain harmful volatile organic compounds such as formaldehyde, which reduces pollution to the environment, meets green environmental protection standards, and reduces potential harm to human health, especially to the respiratory tract and skin; the leak-proof agent of the present invention can be well combined with a variety of substrates to form a strong seal and has good resistance to a variety of chemical substances. At the same time, it has excellent waterproof performance and can still be used when the roof is wet. It has a fast curing speed and can quickly restore the normal use of the building. DETAILED DESCRIPTION
[0020] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.
[0021] The experimental methods in the following examples, unless otherwise specified, are conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0022] Example 1
[0023] 1: Add 100g polyurethane resin and 500ml 9% hydrochloric acid into an oil bath pot, the oil bath pot is equipped with a thermometer and a magnetic stirrer, adjust the oil bath temperature to 90°C, heat the oil bath, adjust the magnetic stirrer stirring rate to 500rpm, stir the acid hydrolysis reaction for 30min, then adjust the temperature to 65°C, set the stirring rate to 400rpm, and stir for 1h to obtain 540ml intermediate A;
[0024] 2: Add 180g of hydroxyethyl cellulose to 540ml of intermediate A, use a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, fill with nitrogen protection, stir and react for 0.5h at a temperature of 40°C and a stirring rate of 400rpm, then heat to 90°C for reflux reaction for 3h, use a magnetic stirrer to set the speed to 300rpm for continuous stirring during the reflux reaction, let it stand after the reflux reaction is completed, observe the thermometer reading, stop standing when the thermometer reading drops to 25°C, then use a vacuum filter to vacuum filter, wash the filter cake with distilled water 5 times, then place it in a vacuum drying oven, and dry it at a temperature of 85°C for 1h to obtain 600ml of intermediate B;
[0025] 3: Transfer 600 ml of intermediate B to a distillation tower, adjust the pressure of the distillation tower to 0.5 atm, and collect the distillation bottom product after distillation for 5 hours; repeat steps A1-A2 twice with the top product of the distillation tower, transfer the distillation bottom product to room temperature and cool it for 1 hour to obtain 260 g of Example 1.
[0026] Table 1, reagent parameters used in Example 1
[0027] Drug Name source model parameter Polyurethane resin Anhui Chunxiao Chemical Co., Ltd. 7118 1kg hydrochloric acid Aladdin H399545 100ml Hydroxyethyl Cellulose Guangdong Zhongke Hongtai New Materials Co., Ltd. C-178 1kg
[0028] Example 2
[0029] 1: 80g polyurethane resin and 400ml 9% hydrochloric acid were added to an oil bath pot, and a thermometer and a magnetic stirrer were installed in the oil bath pot. The oil bath temperature was adjusted to 80°C for oil bath heating, and the stirring rate of the magnetic stirrer was adjusted to 400rpm. After stirring for 30min, the temperature was adjusted to 50°C, the stirring rate was set to 300rpm, and stirred for 1h to obtain 432ml of intermediate A;
[0030] 2: Add 144g of hydroxyethyl cellulose to 432ml of intermediate A, use a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, fill with nitrogen protection, stir and react at a temperature of 40°C and a stirring rate of 400rpm for 0.5h, then heat to 90°C for reflux reaction for 2h, use a magnetic stirrer with a speed set to 200rpm for continuous stirring during the reflux reaction, let it stand after the reflux reaction, observe the thermometer reading, stop standing when the thermometer reading drops to 25°C, then use a vacuum filter to vacuum filter, wash the filter cake with distilled water 3 times, then place it in a vacuum drying oven, and dry it at a temperature of 80°C for 0.5h to obtain 540ml of intermediate B;
[0031] 3: Transfer 540 ml of intermediate B to a distillation tower, adjust the distillation tower pressure to 0.4 atm, and collect the distillation bottom product after distillation for 5 hours; repeat steps A1-A2 twice with the top product of the distillation tower, transfer the distillation bottom product to room temperature and cool it for 0.5 hours to obtain 220 g of Example 2.
[0032] Table 2, reagent parameters used in Example 2
[0033] Drug Name source model parameter Polyurethane resin Anhui Chunxiao Chemical Co., Ltd. 7118 1kg hydrochloric acid Aladdin H399545 100ml Hydroxyethyl Cellulose Guangdong Zhongke Hongtai New Materials Co., Ltd. C-178 1kg
[0034] Example 3
[0035] 1: 90 g of Example 1, 30 g of acrylic acid and 30 g of xanthan gum were added to a reactor, the reaction temperature was adjusted to 100° C., the speed of the magnetic stirrer was set to 1200 rpm and stirred for 30 min, then 20 g of vinyl siloxane was added, and the stirring reaction was continued for 1 h to obtain product 1;
[0036] 2: Product 1 was transferred to a high-pressure reactor, and then 4 g of quartz sand and 4 g of talcum powder were added to the reactor, the pressure of the high-pressure reactor was adjusted to 6.5 MPa, the temperature was adjusted to 80°C, the speed of the magnetic stirrer was set to 1800 rpm and stirred for 30 min to obtain product 2;
[0037] 3: Add 2 g of phenylbenzimidazole and 2 g of benzophenone-1 to product 2, keep the pressure of the autoclave unchanged, adjust the reaction temperature to 52°C, set the speed of the magnetic stirrer to 1000 rpm, and stir for 30 min to obtain product 3;
[0038] 4: Add 4 g of green tea extract and 2 g of butylated hydroxytoluene to product 3, adjust the pressure of the autoclave to 4.2 MPa, the temperature to 62°C, the speed of the magnetic stirrer to 800 rpm, stir the reaction for 30 min, and then stand at normal pressure (0.1013 MPa) for 15 min to obtain 160 g of Example 3.
[0039] Table 3, reagent parameters used in Example 3
[0040]
[0041]
[0042] Example 4
[0043] 1: 120 g of Example 2, 90 g of acrylic acid and 60 g of xanthan gum were added to a reactor, the reaction temperature was adjusted to 100° C., the speed of the magnetic stirrer was set to 1200 rpm and stirred for 30 min, then 45 g of vinyl siloxane was added, and the stirring reaction was continued for 1 h to obtain product 1;
[0044] 2: Product 1 was transferred to a high-pressure reactor, and then 15 g of quartz sand and 15 g of talc were added to the reactor, the pressure of the high-pressure reactor was adjusted to 5.8 MPa, the temperature was adjusted to 65°C, the speed of the magnetic stirrer was set to 1800 rpm and stirred for 30 min to obtain product 2;
[0045] 3: Add 9 g of phenylbenzimidazole and 9 g of benzophenone-1 to product 2, keep the pressure of the autoclave unchanged, adjust the reaction temperature to 45°C, set the speed of the magnetic stirrer to 1000 rpm, and stir for 30 min to obtain product 3;
[0046] 4: Add 15 g of green tea extract and 9 g of butylated hydroxytoluene to product 3, adjust the pressure of the autoclave to 4.0 MPa, the temperature to 60°C, the speed of the magnetic stirrer to 700 rpm, stir the reaction for 30 min, and then stand at normal pressure (0.1013 MPa) for 15 min to obtain 240 g of Example 4.
[0047] Table 4, reagent parameters used in Example 4
[0048] Drug Name source model parameter talcum powder Hebei Hezhen Industrial Co., Ltd. HZ-01 2000 mesh Quartz sand Lingshou County Shuntian Mineral Products Processing Factory ST6548 2000 mesh acrylic acid Aladdin A103526 500g Xanthan gum Shandong Xinhu Biotechnology Co., Ltd. 20115062 1kg Phenylbenzimidazole Hefei Chemik Biochemical Technology Co., Ltd. 716-79-0 500g Benzophenone-1 Shanghai Ruidong Chemical Group Co., Ltd. 178-76-8 1kg Green Tea Extract Shaanxi Honghui Biotechnology Co., Ltd. HH-0333 1kg Butylated Hydroxytoluene Shandong Dejurenhe Chemical Raw Materials 128-37-0 1kg Vinyl siloxane Hubei Langbowan Biopharmaceutical Co., Ltd. 2627-95-4 1kg
[0049] Comparative Example 1
[0050] Example 1 of Chinese patent publication number CN108585735A was selected as comparative example 1.
[0051] Comparative Example 2
[0052] Example 1 of the Chinese patent with publication number CN106634680A was selected as comparative example 2.
[0053] Formaldehyde emission:
[0054] According to the "Determination of Volatile Organic Compounds in Building Decoration Materials" specified in the "GB / T 16423-1996" standard, formaldehyde emission tests were performed on Example 3, Example 4, Comparative Example 1 and Comparative Example 2;
[0055] Table 5, formaldehyde emission test results
[0056]
[0057]
[0058] By analyzing Table 5, it can be seen that the plugging agents prepared in Example 3 and Example 4 do not release formaldehyde during use and have better environmental performance.
[0059] Corrosion test:
[0060] According to the "Test Methods for Physical Properties of Building Decoration Materials and Their Products" specified in the "GB / T 17657-2013" standard, the corrosion resistance test was performed on Example 3, Example 4, Comparative Example 1 and Comparative Example 2;
[0061] According to the "Salt Spray Resistance Test of Coatings" specified in the "GB / T 9271-2008" standard, the salt spray resistance test was performed on Example 3, Example 4, Comparative Example 1 and Comparative Example 2;
[0062] Table 6, Corrosion test results
[0063] (9%NaCl)48h <![CDATA[(10%H2SO4)48h]]> (50%NaOH) 48h Example 3 No abnormality No abnormality No abnormality Example 4 No abnormality No abnormality No abnormality Comparative Example 1 No abnormality Minor damage No abnormality Comparative Example 2 No abnormality No abnormality Minor damage
[0064] By analyzing Table 6, it can be seen that the plugging agents prepared in Example 3 and Example 4 have strong tolerance to acidic, alkaline and neutral environments during actual use, are not prone to damage and have a longer service life.
[0065] Drying and wear resistance test:
[0066] According to the "Determination Method of Drying Time of Coatings" specified in the "GB / T 9276-1998" standard and the "Architectural Coatings Part 2: Determination of Drying Time" specified in the "GB / T13452.2-2008" standard, the drying time performance test was performed on Example 3, Example 4, Comparative Example 1 and Comparative Example 2;
[0067] According to the "Test Methods for Physical Properties of Building Decoration Materials and Their Products" specified in the "GB / T 17657-2013" standard, the wear resistance of Example 3, Example 4, Comparative Example 1 and Comparative Example 2 was tested;
[0068] Table 7, Drying and wear resistance test results
[0069] Surface drying time (min) Shore hardness (D) Wear resistance(N) Example 3 21 86D 26 Example 4 24 87D 27 Comparative Example 1 35 72D 25 Comparative Example 2 37 64D 22
[0070] By analyzing Table 7, it can be seen that the plugging agents prepared in Example 3 and Example 4 have a faster drying time and have better effects in wear resistance and hardness.
[0071] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A leak-proofing agent for building roof repair, characterized in that: It is composed of the following percentage components: 30-45% hydroxyethyl cellulose modified polyurethane resin, 15-30% acrylic acid, 2-5% quartz sand, 2-5% talc, 15-20% xanthan gum, 1-3% phenylbenzimidazole, 1-3% benzophenone-1, 2-5% green tea extract, 10-15% vinyl silicone, 1-3% butylated hydroxytoluene; The preparation method of the hydroxyethyl cellulose modified polyurethane resin comprises the following steps: A1: Add polyurethane resin and 9% hydrochloric acid into an oil bath pot, which is equipped with a thermometer and a magnetic stirrer, adjust the oil bath temperature to 80-90°C for oil bath heating, adjust the magnetic stirrer stirring rate to 400-500rpm, stir for acid hydrolysis reaction for 30min, then adjust the temperature to 50-65°C, set the stirring rate to 300-400rpm, and stir for 1h to obtain intermediate A; A2: Add hydroxyethyl cellulose to intermediate A, use a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, fill with nitrogen protection, stir and react for 0.5 h at a temperature of 30-40°C and a stirring rate of 300-400 rpm, then heat to 80-90°C for reflux reaction for 2-3 h, use a magnetic stirrer with a speed of 200-300 rpm to continuously stir during the reflux reaction, let it stand after the reflux reaction is completed, observe the thermometer reading, stop standing when the thermometer reading drops to 25°C, then use a vacuum filter to vacuum filter, wash the filter cake with distilled water for 3-5 times, then place it in a vacuum drying oven, and dry it at a temperature of 80-85°C for 0.5-1h to obtain intermediate B; A3: Transfer intermediate B to a distillation tower, adjust the pressure of the distillation tower to 0.2-0.5 atm, and collect the distillation bottom product after distillation for 3-5 hours; repeat steps A1-A2 twice for the top product of the distillation tower, transfer the distillation bottom product to room temperature and cool it for 0.5-1 hour to obtain a hydroxyethyl cellulose modified polyurethane resin.
2. A leak-proofing agent for building roof repair according to claim 1, characterized in that: The mass ratio of the polyurethane resin and 9% hydrochloric acid in step A1 is 1:
5.
3. A leak-proofing agent for building roof repair according to claim 1, characterized in that: The mass ratio of the intermediate A and hydroxyethyl cellulose described in step A2 is 3:
1.
4. A leak-proofing agent for repairing a building roof according to claim 1, characterized in that: The talcum powder has a silicon content of 60% and a particle size of 2000 meshes.
5. A leak-proofing agent for building roof repair according to claim 1, characterized in that: The quartz sand is quartz sand powder with a silicon dioxide content of 99% and a particle size of 2000 meshes.
6. A leak-proofing agent for building roof repair according to claim 1, characterized in that: The green tea extract is water-soluble green tea extract powder with a specification of 15:
1.
7. The method for preparing a leak-proofing agent for building roof repair according to claim 1, characterized in that The following steps are involved: B1: Preparation of hydroxyethyl cellulose modified polyurethane resin; B2: Add hydroxyethyl cellulose modified polyurethane resin, acrylic acid and xanthan gum into the reactor, adjust the reaction temperature to 80-100°C, set the speed of the magnetic stirrer to 1000-1200 rpm and stir for 30 min, then add vinyl siloxane, continue stirring and reacting for 1 h to obtain product 1; B3: Product 1 was transferred to a high-pressure reactor, and then quartz sand and talcum powder were added to the reactor, the pressure of the high-pressure reactor was adjusted to 5.8-6.5 MPa, the temperature was adjusted to 65-80°C, and the speed of the magnetic stirrer was set to 1500-1800 rpm and stirred for 30 min to obtain product 2; B4: Add phenylbenzimidazole and benzophenone-1 to product 2, keep the pressure of the autoclave unchanged, adjust the reaction temperature to 45-52°C, set the speed of the magnetic stirrer to 800-1000 rpm, and stir for 30 minutes to obtain product 3; B5: Add green tea extract and butylated hydroxytoluene to product 3, adjust the pressure of the autoclave to 3.4-4.2 MPa, the temperature to 54-62°C, and the speed of the magnetic stirrer to 600-800 rpm. After stirring for 30 minutes, let it stand at normal pressure (0.1013 MPa) for 15 minutes to obtain a plugging agent for repairing building roofs.
Citation Information
Patent Citations
Resin matrix glass fiber reinforced plastic and preparation method thereof
CN118956100A
